Identification of alpha-glucosidase inhibitors in Cosmos caudatus leaves using GC-MS based metabolomics - Khatib, Alfi; Javadi, Neda; Abas, Faridah; Abdul Hamid, Azizah; Simoh, Sanimah; Shaari, Khozirah; Ismail, Intan Safinar; Mediani, Ahmed (2015)
Cosmos caudatus (“Ulam Raja” in Malaysia) is a plant used in Malaysia to enhance vitality and has been studied for its antidiabetic activity. This study focused on the evaluation of the α-glucosidase inhibitory activity of different ethanolic extracts of C. caudatus. Six series of samples extracted with water, 20%, 40%, 60%, 80%, and 100% ethanol were employed. Gas chromatography-mass spectrometry (GC-MS) and multivariate data analysis was used to correlate bioactivity of different extracts to different metabolite profiles of C. caudatus. The obtained loading scores indicated a distinct and remarkable separation into 6 clusters, which were indicative of the 6 different quality of samples. GCMS can be integrated with multivariate data analysis to identify compounds that inhibit α-glucosidase activity. Through this approach several chemical makers e.g. catechin, α-linolenic acid, α-D-glucopyranoside, and vitamin E compounds were identified as an α-glucosidase inhibitors of this herb.